Semantica, metafisica e competenza linguistica: l’eredità di Dummett - Vignolo, Massimiliano (Rivista Italiana di Filosofia del Linguaggio)
Throughout his philosophical career, Michael Dummett held firmly two theses: (I) the theory of meaning has a central position in philosophy and all other forms of philosophical inquiry rest upon semantic analysis, in particular semantic issues replace traditional metaphysical issues; (II) the theory of meaning is a theory of understanding. I will defend neither of them. However, I will argue that there is an important lesson we ought to learn by reflecting on the link between linguistic competence and semantics, which I take to be an important part of Dummett’s legacy in philosophy of language. I discuss this point in relation to Cappelen and Lepore’s criticism of Incompleteness Arguments.